Сорбція індустріального масла спученим графітом - Lazareva, N. I.; Mysyk, R. D.; Shologon, V. I.; Yaroshenko, O. P.; Savos'kin, M. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2004)
The sorption of industrial oil from its water emulsion by exfoliated graphite was shown to be about 20 g/g what is 3.5 times lower than that in case of pure oil. The material sorption capacity is determined mainly (for 60 %) by specific surface area, the rest (40 %) being provided due to its specific volume.